Hygiene Status and Meat Handling Practices in Retail Poultry Meat Shops of Nagpur City of Maharashtra - Rathod, Kishor; BL, Mundhe; SR, Badhe (Journal of Meat Science, 2023)
Poultry retail meat shops are endpoints in the meat chain and can have a determinant role in cross-contamination control. Considering this, a total of 160 retail poultry meat shops in and around Nagpur city of Maharashtra state were assessed for hygienic status and meat handling practices. Meat handlers from poultry meat shops were interviewed through a structural questionnaire. It was found that 83.7% of meat shops had no provision of separate docks for edible and inedible products. In terms of design and facilities, only 27.5% of shops had the facility of flyproof windows. 80.6% of meat shop workers lack training in handling meat and equipment. It was observed that about 83.1% of meat shop workers do not wash their hands properly before entering and leaving the meat shop. About 25% of meat shops do not have any arrangement for the disposal of waste material. Considering the findings to improve the hygienic status and reduce transmission of diseases due to consuming contaminated meat, regular surveillance of poultry shops and formal training of butchers are necessary.